German minority in urban space of a textile manufacturing centre: the case of 19th century city of Łódź - Marszał, Tadeusz (European Spatial Research and Policy, 2024)
German settlement in Poland has been the subject of numerous studies. The causes and determinants of migratory movements have been discussed extensively, while little attention has been paid to the spatial aspects of the phenomenon. The aim of this study, which is part of geographical and historical research, is to determine the size of the influx of migrants of German nationality into the rapidly developing textile production centre of Łódź in the 19th century, as well as the geographical origins and distribution of this nationality group in the urban space. These considerations are complemented by the identification of key issues related to the social integration and assimilation processes of the German minority. In the first half of the 19th century, the influx of skilled labour, almost entirely recruited from the German population, conditioned the development of the textile industry in Łódź. It also had a key influence on the demographic development of Łódź, which soon became the largest centre of textile production in Poland. In subsequent decades, there was a tendency among German immigrants towards separation in the sphere of professional and social activities, but already by the end of the 19th century the German community settled in Łódź was diverse in terms of the sense of nationality. In addition to a certain proportion of the immigrants who were already Polonised, there were persons declaring German nationality, as well as those undecided about the issue.